Convergence of Faith and Capital Analysis of the Implementation of Sharia-Based Financial Institutions in Malaysia - Lukman Yafi (Solo International Collaboration and Publication of Social Sciences and Humanities, 2024)
The purpose of this study is to analyze the convergence of faith and capital in the application of Sharia-based financial institutions in Malaysia. The research methods used include literature studies, secondary data analysis, and interviews with experts and practitioners of the Islamic financial industry. This study identifies factors that influence the convergence of faith and capital in the context of Islamic financial institutions, including regulation, culture, and the level of public understanding of sharia principles. The results show that the convergence of faith and capital in the implementation of Sharia-based financial institutions in Malaysia still faces several challenges, including gaps in understanding of Sharia principles among the public, different interpretations of regulations, and a lack of adequate support infrastructure. Nevertheless, there have been positive developments in terms of the growth of Islamic financial institutions and increased awareness of the importance of Sharia-based finance in Malaysia. This research contributes to the understanding of the dynamics of the convergence of faith and capital in the context of Islamic financial institutions in Malaysia as well as provides insight for decision-makers, regulators, and practitioners of the Islamic financial industry in overcoming challenges and seizing future opportunities.